Utilization of Tithonia diversifolia and sugarcane leaves to improve soil properties and plant growth on a sandy soil of Malang, East Java - Yulfita Farni; Retno Suntari; Sugeng Prijono (Journal of Degraded and Mining Lands Management, 2022)
A study on the addition of organic matter of different qualities was carried out to improve plant growth on a degraded sandy soil of Bambang Village, Wajak Malang, East Java. Two potential sources of organic matter in Bambang Village are Tithonia diversifolia and sugarcane leaves. This study aimed at elucidating the changes in some chemical properties of a degraded sandy soil of Malang, East Java, and nutrient uptake and growth of maize plants by applying mixtures of Tithonia diversifolia and sugarcane leaves of different quality. Treatments tested in this study were mixtures of Tithonia diversifolia leaves and sugarcane leaves at various proportions (%w/w), i.e. 100% Tithonia diversifolia leaves (T1), 100% sugarcane leaves (T2), 75% Tithonia diversifolia leaves + 25% sugarcane leaves (T3), 50% Tithonia diversifolia leaves + 50% sugarcane leaves (T4); without organic matters (T6), and control, without organic matter and inorganic fertilizers (T7). The results showed that the application of Tithonia diversifolia and sugarcane leaves affected soil pH, soil exchangeable bases, maize growth, and nutrients uptake. Nutrients taken up by maize plants significantly increased with the addition of Tithonia diversifolia leaves, either alone or in combination with sugarcane leaves. The application of 100% sugarcane leaves did not significantly affect maize growth and nutrient uptake.